Caracterización geográfica de cepas de fusarium. Que afecta al cultivo de clavel (dianthus caryophyllus) en el cantón Latacunga. - Salas Tigrero, Liseth Jessabeth (2022)
The investigation of "GEOGRAPHICAL CHARACTERIZATION OF STRAINS OF Fusarium IN THE CROP OF CARNATION (Dianthus caryophyllus) IN THE CANTON LATACUNGA.", the strains collected from the carnation crop were evaluated. Carnation samples with disease symptoms were collected for identification. The present investigative work was carried out in the Latacunga canton in the parishes: Eloy Alfaro, Tanicuchi, Alaquez, Guaytacama, Poalo, Toacaso and Belisario Quevedo. Sampling was carried out from 2020 to 2021. The research was carried out in two phases: one in the field and the other in the laboratory. The field work was carried out in collecting carnation samples with symptoms of the disease for their identification. Once the samples with symptoms were obtained, the identification in the laboratory was carried out as follows: Isolation of fungi Isolation of pure cultures, Morphological identification. In the Latacunga canton, 3 strains of the Fusarium genus were identified, which are: Fusarium oxysporum, Fusarium solani and Fusarium sp. In the Tanicuchi, Joseguango, Belisario Quevedo, Guaytacama, Toacaso and Poalo parishes, two strains were identified: Fusarium oxysporum and Fusarium solani: and in the Eloy Alfaro, Alaquez and Guaytacama parishes three strains were identified: Fusarium oxysporum, Fusarium solani and Fusarium sp. Fusarium oxysporum adapts to the three climatic floors, such as: low, medium and high: Fusarium solani adapts to two climatic floors, such as: medium and high: Fusarium sp., we have that it only adapts to one climatic floor, which is medium. The average values of incidence of Fusarium vary between: F. oxysporum with an incidence of 67%, which is more likely due to problems of the composition of the medium or habitat, pH and temperature; therefore F. solani is with an incidence of 26% and F. sp with an incidence of 7%